A Longitudinal Study of the Effect of Organized Physical Activity on Free Active Play. Issue 9 (September 2018) - CAIRNEY, JOHN; BULTEN, RHEANNA; KING-DOWLING, SARA; ARBOUR-NICITOPOULOS, KELLY
ABSTRACT: Purpose: The relationship between organized sport participation and positive youth development is well established. However, overinvolvement in sport and organized physical activity has been identified as having a potentially negative effect. Overscheduling and its impact on free play is one concern, given the importance of free play to overall health and development. Currently, it is not known if greater participation in organized sport has a positive or negative effect on discretionary free play in children and youth. Methods: The Physical Health and Activity Study Team study was a 5-yr, longitudinal cohort study that followed 2278 fourth grade children (ages 9–10 yr). Organized sport and free play was assessed in the fall of each school year from fifth to eighth grades using self-report questionnaires. Results: Using mixed-effects modeling, we found that higher participation in organized sport was associated with increased participation in free play over time (coefficient = 0.20, P < 0.001). Although this effect was independent of age and socioeconomic status, we did find that boys with high levels of organized participation reported the highest levels of free play overall. Conclusions: Possible explanations for this association are related to the role sport might play in supporting physical literacy and the development of fundamental movement skills, allowing children to participate in more active free play pursuits. It might also be the case that active children simply seek out both organized and unorganized physical activity opportunities during this developmental period. Limitations and implications for further research and policy are discussed.